2019
DOI: 10.3390/ijerph17010104
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Adolescents’ Need Support, Need Satisfaction, and Health-Related Outcomes: A Self-Determination Health Behavior Perspective

Abstract: School physical education (PE) as an important social context can promote adolescents' physical health and contributes to their mental health. Guided by the self-determination health behavior model, the study aimed to examine a structural mediation model to investigate the relationships among perceived need support from PE teachers, psychological need satisfaction, and adolescents' health-related outcomes. Participants were 300 adolescents (M age = 14.48; 50.3% girls) recruited from five middle schools in Shan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Such efforts can address the health and PA disparity issues in underserved Hispanic children [16]. Last but not least, school PA specialists and health promoters may provide a learning environment emphasizing self-improvement instead of peer comparison for children's goal-setting and skill practices in PE and recess programs [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such efforts can address the health and PA disparity issues in underserved Hispanic children [16]. Last but not least, school PA specialists and health promoters may provide a learning environment emphasizing self-improvement instead of peer comparison for children's goal-setting and skill practices in PE and recess programs [10].…”
Section: Discussionmentioning
confidence: 99%
“…HRQoL includes physical and psychosocial functioning [4], which is one of the essential components of health-related outcomes of diverse clinical interventions for practitioners, researchers, and patients [5]. Previous research has demonstrated that childhood obesity, as a result of physical inactivity, is associated with lower HRQoL [6,7] and depression [8], and that greater PA participation is associated with higher HRQoL among school-aged children [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Children were more likely to experience enjoyment once they were competent in different ball skills, which in turn promoted their PA participation. Echoing the suggestions of previous studies [ 5 , 7 , 50 ], PE teachers should aim at improving students’ ball skills with a need-supportive environment that encourages them to feel competent to engage in various types of games and that promotes PA enjoyment.…”
Section: Discussionmentioning
confidence: 99%
“…As an analogy, Chen et al (2019) found that BPNS mediates the relationship between perceived need support from physical education teachers and adolescents’ health-related outcomes. In addition, Shao et al (2018) demonstrated that the parent–child cohesion has a negative impact on LBC’s depression and loneliness through the partial mediation of BPNS.…”
Section: Introductionmentioning
confidence: 99%